Trans-1,2-Dicyano-cyclopropane and Other Cyano-cyclopropane Derivatives : a theoretical and experimental VA, VCD, Raman and ROA spectroscopic study. - Jalkanen, Karl; Gale, Julian; Jalkanen, G.; McIntosh, D.; El-Azhary, A.; Jensen, G. (2007)
In this work we present the experimental vibrational absorption (VA), vibrational circular dichroism(VCD) and Raman spectra for (+)-trans-1(S),2(S)-dicyanocyclopropane and its dideuterio derivative, trans-1(S),2(S)-dicyano-1(S),2(S)-dideuteriocyclopropane, along with VA, VCD, Raman and Raman optical activity (ROA) spectral simulations. Here we investigate the applicability of various local and non-local exchange-correlation (XC) functionals, hybrids and meta-hybrids to reproduce the vibrational spectra of this strained ring system, which also bears two cyano groups. At the highest level of theory, B3PW91/ aug-cc-pVTZ, we also investigated the trans-, cis- and gemdicyanocyclopropane(trans-, cis-, and gem-DCCP), cyanocyclopropane (CCP) and the parent molecule cyclopropane(CP). In doing so we have investigated the electronic effects (coupling) between the cyano groups and the cyclopropane ring. In addition to providing an interpretation of the experimentally observed vibrational spectra for these molecules, this work also provides benchmark calculations for othermethods, especially semi-empirical based wave function and density functional theory (DFT) based methods, such as SCCDFTB and PM6. For the semi-empirical DFT based methods to be used for 3-membered ring systems, one ought to document their reliability for systems which were not used inthe parameterization. The small 3- and 4-membered ring systems are good test systems because they contain non-standard bonding, whichmay be difficult to determine accurately with the approximations used in the SCC-DFTB and other semiempirical methods. Like molecular mechanics force fields,semi-empirical methods, based on DFT and wave function quantum mechanics (WFQM),must be benchmarked against high level ab initio and DFT calculations and experimental data. In addition to bonding, the changes in the electric dipole moment, magnetic dipole moment, electric dipole-electricdipole polarizability, electric dipole-magnetic dipole polarizability and electric dipole-electric quadrupole polarizability with respect to nuclear displacement and nuclear velocity can be determined by the VA, VCD, Raman and ROA intensities. Hence it is important that the semi-empirical based DFT andwave function methods not only be parameterized to determine energies, gradients and Hessians, but also the electric and magnetic moments and their derivatives that determine the electronic and magnetic properties of these molecules and their interactions with matter and radiation. This will allow biochemists, biophysicists, molecular biologists, and physical biologists to use experimental and theoretical VA, VCD, Raman and ROA spectroscopies to probe biophysical and biochemical function and processes at the molecular level.